Fluid absorption in the isolated midgut of adult female yellow fever mosquitoes (Aedes aegypti) - Onken, Horst (J Exp Biol, 2015)
The transepithelial voltage (V(te)) and the volume of isolated posterior midguts of adult female yellow fever mosquitoes (Aedes aegypti) were monitored. In all experiments, the initial V(te) after filling the midgut was lumen negative, but subsequently became lumen positive at a rate of approximately 1 mV min(−1). Simultaneously, the midgut volume decreased, indicating spontaneous fluid absorption. When the midguts were filled and bathed with mosquito saline, the average rate of fluid absorption was 36.5±3.0 nl min(−1) (N=4, ±s.e.m.). In the presence of theophylline (10 mmol l(−1)), V(te) reached significantly higher lumen-positive values, but the rate of fluid absorption was not affected (N=6). In the presence of NaCN (5 mmol l(−1)), V(te) remained close to 0 mV (N=4) and fluid absorption was reduced (14.4±1.3 nl min(−1), N=3, ±s.e.m.). When midguts were filled with buffered NaCl (154 mmol l(−1) plus 1 mmol l(−1) HEPES) and bathed in mosquito saline with theophylline, fluid absorption was augmented (50.0±5.8 nl min(−1), N=12, ±s.e.m.). Concanamycin A (10 µmol l(−1)), ouabain (1 mmol l(−1)), and acetazolamide (1 mmol l(−1)) affected V(te) in different ways, but all reduced fluid absorption by 60–70% of the value before addition of the drugs.